2019
DOI: 10.1007/s00125-019-4910-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting gut microbiota and barrier function with prebiotics to alleviate autoimmune manifestations in NOD mice

Abstract: Aims/hypothesis Adopting a diet containing indigestible fibre compounds such as prebiotics to fuel advantageous bacteria has proven beneficial for alleviating inflammation. The effect of the microbial changes on autoimmunity, however, remains unknown. We studied the effects of prebiotic xylooligosaccharides (XOS) on pancreatic islet and salivary gland inflammation in NOD mice and tested whether these were mediated by the gut microbiota. Methods Mother and offspring mice were fed an XOS-supplemented diet until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Although TNF-α was slightly upregulated after surgery, there was no significant difference among four groups, which indicated that TNFα may not be the major inflammatory cytokines for the postoperative neuroinflammatory response and cognitive dysfunction in the present model. Furthermore, intestinal barrier damage and increased inflammation response can be attenuated by XOS intervention through modulating the intestinal microbiota, which is consistent with the anti-autoimmune effect of XOS in non-obesity-diabetes mice [53]. Evidence has proven that XOS intervention can reduce intestinal permeability markers and inflammatory response through inhibiting of natural killer T cells and cytotoxic T cells [53], which require further investigations in the perioperative context.…”
Section: Discussionsupporting
confidence: 63%
“…Although TNF-α was slightly upregulated after surgery, there was no significant difference among four groups, which indicated that TNFα may not be the major inflammatory cytokines for the postoperative neuroinflammatory response and cognitive dysfunction in the present model. Furthermore, intestinal barrier damage and increased inflammation response can be attenuated by XOS intervention through modulating the intestinal microbiota, which is consistent with the anti-autoimmune effect of XOS in non-obesity-diabetes mice [53]. Evidence has proven that XOS intervention can reduce intestinal permeability markers and inflammatory response through inhibiting of natural killer T cells and cytotoxic T cells [53], which require further investigations in the perioperative context.…”
Section: Discussionsupporting
confidence: 63%
“…A more pronounced regional and systemic anti-inflammatory environment was also observed compared with the control group (105)(106)(107)(108)(109)(110). Hence, this treatment may serve to improve gut barrier and, thus, has the potential to activate autoreactive immune responses (104).…”
Section: Intestinal Flora Can Be Used To Reconstruct Regional Immunitmentioning
confidence: 89%
“…The mechanism by which intestinal flora affects the regional immune system includes secretion of metabolic products (6), expression of PAMPs (9), and prevention of pathogen adhesion (103). For example, probiotics including bifidobacteria and lactobacilli, affect autoimmunity (104). This has been supported by a study that fed non-obese diabetic mouse a xylooligosaccharide diet and observed a subsequent reduction in intestinal marker permeability, primarily from M1 to M2 macrophages, an increase in the activation of regulatory T cells, and a reduction in the levels of activated cytotoxic T cells and NKT cells.…”
Section: Intestinal Flora Can Be Used To Reconstruct Regional Immunitmentioning
confidence: 99%
“…Therefore, prebiotics, the substrates that are selectively utilized by host microorganisms conferring a health benefit [ 21 ], were proposed as a promising intervention for gut barrier improvement [ 22 , 23 ]. The positive effects of prebiotics and prebiotic-derived metabolites on the gut barrier functions have been repeatedly confirmed by in vitro and in vivo studies [ 24 , 25 , 26 ]. However, there is no agreement in the influence of prebiotics in clinical trials.…”
Section: Introductionmentioning
confidence: 92%